Off-axis stability of intense continuous relativistic beams - Martins L.C.* (2009)
This paper investigates the stability of off-axis continuous intense relativistic beams propagating inside a circular conducting pipe. The equations of motion for the centroid and the envelope of slightly off-axis beams are derived and used to determine equilibrium and stability conditions for the beam transport. It is shown that depending on the parameters of the system, beams propagating along the pipe axis may become unstable due to the presence of the wall, imposing a fundamental limitation in the effective area that an equilibrium beam can occupy inside the conductor. © 2009 American Institute of Physics.